2018
DOI: 10.1186/s12890-018-0692-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of community-based and home-based pulmonary rehabilitation for pneumoconiosis patients: a retrospective study

Abstract: BackgroundPneumoconiosis patients receive community-based or home-based pulmonary rehabilitation (PR) for symptom management and enhancement of physical and mental well-being. This study aimed to review the clinical benefits of community-based rehabilitation programmes (CBRP) and home-based rehabilitation programmes (HBRP) for PR of pneumoconiosis patients.MethodsArchival data of pneumoconiosis patients who participated in CBRP and HBRP between 2008 and 2011 was analysed. There were 155 and 26 patients in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 41 publications
3
36
0
1
Order By: Relevance
“…Randstrom et al (2014) reported that giving older people the opportunity to do for themselves or "hands-off" was a vital part of rehabilitation services in the home. The vast benefits associated with "hands-off" community rehabilitation are well established in the literature (Augustine et al, 2020;Luker et al, 2019;Tsang et al, 2018;van Isselt et al, 2018). Metzelthin et al (2017) described a program in the Netherlands with an emphasis on equipping home support workers with the necessary knowledge, attitude, skills and organisational support to deliver daily services at home from a more rehabilitative perspective of doing with rather than for, an approach in keeping with reablement.…”
Section: Discussionmentioning
confidence: 99%
“…Randstrom et al (2014) reported that giving older people the opportunity to do for themselves or "hands-off" was a vital part of rehabilitation services in the home. The vast benefits associated with "hands-off" community rehabilitation are well established in the literature (Augustine et al, 2020;Luker et al, 2019;Tsang et al, 2018;van Isselt et al, 2018). Metzelthin et al (2017) described a program in the Netherlands with an emphasis on equipping home support workers with the necessary knowledge, attitude, skills and organisational support to deliver daily services at home from a more rehabilitative perspective of doing with rather than for, an approach in keeping with reablement.…”
Section: Discussionmentioning
confidence: 99%
“…La dimensión de actividad parece tener un mayor impacto al momento de evaluar los cambios percibidos después de su participación en el programa educativo multidisciplinar. Una revisión realizada por Cochrane, donde se examinaron 26 ensayos clínicos con 2997 pacientes con seguimientos entre 3 a 24 meses en programas de manejo integrado para EPOC demostró cambios significativos en el dominio actividad, hallazgo similar al encontrado en nuestro estudio, al igual que alcanzó la diferencia clínicamente relevante de cuatro unidades solo para el dominio de impacto [25][26][27][28] . La rehabilitación pulmonar ha reflejado a través de diferentes estudios, impactos significativos sobre la calidad de vida de los pacientes con patologías pulmonares crónicas [13][14][15][16] , de tal forma que se sugiere la rehabilitación pulmonar como un complemento al tratamiento médico a partir de un manejo integral de los pacientes 17,29,30 .…”
Section: Discussionunclassified
“…IPF patients have improved maximum exercise capacity and reported less shortness of breath and better quality of life after rehabilitation (36). Home-based programs are a convenient option, since they are effective, simple and an alternative for ILD patients who have restrictions accessing rehabilitation centers (37)(38)(39); moreover, this delivery model enable the interaction in order to propose changes in home environments, train family members and caregivers, as well as trying to develop skills in the patients' daily routine (37).…”
Section: Pr Delivered In Ildsmentioning
confidence: 99%